Análisis de las implicaciones fiscales para Colombia por efecto del TLC con la Unión Europea (2018)
Analysis on the tax implications for external IVA and tariff desgravamen, After the entry into force in 2013 of the TLC with the European Union. By comparing these taxes, and demonstrating positive behavior for external IVA and unfavorable for tariff elimination for the revenue of the nation, showing that in some measure, external VAT manages to compensate for the tax exception of the products.